Adverse effects of crystalloid cardioplegia and slow cooling for protection of immature rat hearts - Karck, Matthias; Schnabel, Philipp Albert; Kilkowski, Andreas; Schulte, Steffen; Haverich, Axel (The annals of thoracic surgery, 1996)
Background - Studies on the benefit of methods for protection of the hypertrophied immature myocardium are rare and controversial. - Methods - We assessed the effects of (1) rapid cooling by topical hypothermia alone, (2) slow prearrest cooling by coronary perfusion hypothermia, and (3) cardioplegic cardiac arrest with St. Thomas’ Hospital solution no. 2 for protection of isolated immature rat hearts (age, 28 days) during 8 hours of global ischemia at 10°C. Myocardial hypertrophy was induced noninvasively by lifelong feeding of a low iron diet. Recovery of left ventricular function, metabolism, and myocardial fine structure were assessed. - Results - In hypertrophied hearts, protection by topical hypothermia alone resulted in significantly improved postischemic recoveries of maximum left ventricular pressure and rate of pressure rise compared with the method of slow cooling or application of cardioplegia (40.6%±5.0% and 38.1%±5.9%, mean±standard error of the mean; p < 0.05). The same pattern of recovery was observed among nonhypertrophied control hearts. Regardless of the method of protection, hypertrophied hearts revealed a significantly larger interstitial space at the end of reperfusion than control hearts. In hypertrophied hearts, postischemic adenosine triphosphate concentrations were higher with topical hypothermia alone for protection than with the other methods. - Conclusions - Rapid cooling by topical hypothermia alone provides superior protection of hypertrophied immature rat hearts as compared with slow prearrest cooling. Application of St. Thomas’ Hospital cardioplegic solution no. 2 does not improve protection and even hinders postischemic functional recovery.
Online veröffentlicht am 1. Januar 1998
Gesehen am 25.01.2022